Impact of Healthcare on Autism and Targets for Future Improvement - Wu, Yixi (Transactions on Social Science, Education and Humanities Research, 2024)
Autism spectrum disorder is a developmental disorder that can cause abnormalities in social behavior, language development, and more. In recent years, neurodiversity has viewed autism as a part of identity, represented as a difference between people rather than a disorder that requires treatment. While the debate about autism has not stopped, as society becomes more widely aware of and concerned about autism, more and more people are beginning to leave misconceptions behind and consider this diverse drama in the context of health care and how to help them. The health care system should recognize the challenges and injustices faced by autistic individuals, understand the complications and other social difficulties that they may face, and make enhancements and improvements to the health care system based on their needs. At all ages, autistic people face different challenges and have different needs, this paper takes a chronological view of the needs of autistic people from early childhood to old age, and how the healthcare system can be enhanced to cater to these needs and better provide help and support to autistic people.